Reflexión crítica sobre la intervención con mujeres víctimas de violencia de género - Méndez Martínez, Concha; Álvarez-buylla Bustillo, Susana (Cuadernos de Trabajo Social, 2007)
Work with victims of violence against women confronts us with a reality that is not at all pretty. Laws passed to address the problem have not succeeded in capturing its essence. We could say that social consciousness has been raised, but the gaps and failures in treating these cases are still evident. A multitude of professionals from all disciplines who work in this area experience a high degree of frustration since the problem has only grown. Simultaneously, the feminization of the professional sector that aids the victims acts as an amplifier which helps make intervention with women more complex. The shadow of a feminine identity tied to the ideas of care and selflessness is making work with victims difficult. Only a pact among women in search of new models of reference can guarantee a real change and be a hope for the future.